Analisis Kinerja Apotek yang Bekerjasama dengan Jaminan Kesehatan Nasional (JKN) dari Perspektif Keuangan dan Pelanggan di Kota Makassar - Maulana, Ilham; Anggriani, Yusi; Aritonang, MGS (Journal of Islamic Pharmacy, 2020)
This study aims to measure the performance of pharmacy inan in the (National Health Insurance) JKN era based ona financial perspective with parameters the net profit margin and pharmacy income. And the perspective customer is within the parameters of the quality pharmacy service in this matter tangibles  , reliability, responsiveness, assurance, and empathy in a pharmacy in Makassar city on customer satisfaction pharmacy and the number of customer visits to the pharmacy. This study employed analytic quantitave and qualitative methods. The research sample consisted of 5 apothecary 99 pharmacy customers. The study results on the financial perspektive show that the net profit margin pharmachie’s 2014 average value was 6,31% and that by 2018 it was 6,93% and the pharmacies were virtually in good condition. In the pharmacies income there are 2 pharmachies that have suffered a decline in the pharmacy’s turnover and 3 pharmachies have experienced an increase in the 2018 over 2014. As for the number of pharmcy customers, there is 1 pharmacy that has a decline and 4 pharmacy that have seen an increase in the number of customer visits to the pharmcy in 2018 over 2014.And the customer perspective, the test F show that the F Count of 5,111 and F Tables 2,31, so that it can be reached the conclusion that the quality of service made up of both reliabilty, tangible, responsiveness, assurance and emphaty affect the  satisfaction of the pharmacies customers in the city of Makassar.   Keywords: financial perspective, customer  satisfaction, pharmacy service’s quality, National Health Insurance